O corpo e a corporeidade na educação infantil: análise de dissertações e teses (2010 – 2016) - Souza, Sandra Rosa Almeida (2017)
The present research aims to analyze master dissertations and doctoral theses produced in public and private universities of the different regions of Brazil that discuss Body and Body in Early Childhood Education, in the period from January 2010 to September 2016. We try to answer the following question: Which are the theoretical references most used in the analyzed works? The documents analyzed were: National Curriculum Framework for Early Childhood Education (RCNEI) and Curricular Guidelines for Early Childhood Education. The research universe was the Coordination of Improvement of Higher Education Personnel (Capes) and the Brazilian Institute of Information and Technology (IBICT) through the Brazilian Digital Library of Theses and Dissertations (BDTD) from January 2010 to September 2016, only in the area off education. In orders to substantiate the body and corporeity categories, we have recourse to different authors who discuss body and body, among them: Bueno (2013), Foucault (1987), Freire (2010), Freire and Scaglia (2007), Galvão), Gonçalves (2014), Oliveira (2010), Silva (2009) and Wallon (2008). It is a research of a qualitative nature, of a bibliographical and documentary nature. Like part of the results, aims, of the ten papers analyzed, Wallon, Freire and Foucault were the most used classic references. Based on this data, we present to the reader what each of these authors understand by body and corporeality, bringing to the fore the categories listed in their theories.